2001
DOI: 10.1034/j.1398-9995.2001.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of natural rubber latex allergy in adults is increased after multiple operative procedures

Abstract: A remarkable percentage of unselected adult patients undergoing surgical procedures have allergy or sensitization to NRL. Repeated invasive treatment appears to be a risk factor for NRL allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 38 publications
0
15
0
2
Order By: Relevance
“…Studies conducted in adult patients with a condition other than myelomeningocele demonstrated that having more than 10 surgeries was significantly associated with latex allergy (p < 0.001). 17 The most significant data obtained from this study is that having more than five surgeries was a risk factor associated with latex allergy in this population. The same number of surgeries was also observed by Michael, et al, who assessed a population of German children with myelomeningocele.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies conducted in adult patients with a condition other than myelomeningocele demonstrated that having more than 10 surgeries was significantly associated with latex allergy (p < 0.001). 17 The most significant data obtained from this study is that having more than five surgeries was a risk factor associated with latex allergy in this population. The same number of surgeries was also observed by Michael, et al, who assessed a population of German children with myelomeningocele.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, different authors have stated that spina bifida itself is an independent risk factor for latex allergy. 16,17 It has been demonstrated that the number of surgeries, especially in the first year of life, is the most important risk factor for sensitization and it is directly related to higher levels of latexspecific IgE. 6,16 Degenhardt, et al 16 assessed 86 patients (mean age: 10.2 years old) with a history of gastrointestinal or urological surgical procedures and found that having more than eight surgeries in the first year of life significantly increased the risk of latex allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Children with spina bifida have a particularly high rate of latex sensitization, with a prevalence of 37% reported in Australia [34], 40% in Europe [35] and 60% in the United States [36]. The experience of multiple surgical procedures exposes these children to a range of rubber products from an early age [37] and is a risk factor for latex allergy [11,12,15] (Table 1). Although efforts to reduce latex exposure during surgery have [25,26] reduced sensitization, especially to proteins of dipped latex products [38,16], the frequent use of in-dwelling catheters may continue to expose these children to the latex proteins of solid rubber products.…”
Section: Latex Allergy -Evolution Of An Epidemic and Beyondmentioning
confidence: 96%
“…The correlation of repeated surgeries and latex sensitization was described in several studies [28,[75][76][77][78]. The principles of a latex prophylaxis programme were published by the Task Force on Allergic Reactions to Latex in 1993 ( Table 2) at the American Academy of Allergy and Immunology [23].…”
Section: Effects Of Latex Prophylaxismentioning
confidence: 99%